UPAYA PENYANDANG DISABILITAS FISIK TERHADAP AKSES PEKERJAAN DALAM PEMENUHAN KEBUTUHAN SOSIAL EKONOMI (Studi Pada Perkumpulan Penyandang Disabilitas Indonesia (PPDI) Provinsi Sulawesi Tenggara) - Wahyuningsi, Pirda; Moita, Sulsalman; Tanzil, Tanzil (WELL-BEING: Journal of Social Welfare, 2021)
Persons with disabilities are every person who experiences physical, intellectual, mental and or sensory limitations for a long period of time who in interacting with the environment experiences obstacles and difficulties to participate fully and effectively with other citizens based on equal rights, a physical disability is someone who has body abnormalities in the locomotion which include bones, muscles and joints that prevent them from doing proper activities. The purpose of this research is to find out the efforts of persons with physical disabilities and the challenges experienced by persons with physical disabilities in accessing jobs in meeting socio-economic needs. This research method is descriptive qualitative. The results showed that first, the efforts made by members of PPDI Sultra in meeting their socio-economic needs, namely increasing self-confidence by working and also joining an environment that has conditions like them so that they can encourage each other and also by participating in training for people with disabilities. gain knowledge and skills to equip them to open and get jobs as well as entrepreneurship, entrepreneurship, namely sewing, welding workshops, and selling groceries. Second, the challenges experienced by PPDI Sultra members with regard to access to jobs in meeting socio-economic needs, namely employment opportunities that are not disability friendly, shame, job opportunities, education and skills. With the efforts made by persons with physical disabilities to access work in meeting their socioeconomic needs, they get recognition from the community that they are able to have a job and fulfill their needs.